2001
DOI: 10.1128/iai.69.4.2527-2534.2001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chicken Mucosal Immune Response toEimeria tenellaandEimeria maximaInfection by Quantitative Reverse Transcription-PCR

Abstract: The recent cloning of chicken genes coding for interleukins, chemokines, and other proteins involved in immune regulation and inflammation allowed us to analyze their expression during infection with Eimeria. The expression levels of different genes in jejunal and cecal RNA extracts isolated from uninfected chickens and chickens infected with Eimeria maxima or E. tenella were measured using a precise quantitative reverse transcription-PCR technique. Seven days after E. tenella infection, expression of the proi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
102
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(123 citation statements)
references
References 43 publications
(37 reference statements)
16
102
1
4
Order By: Relevance
“…In this experiment, dietary CLA did not change the percentage of duodenal CD4 + T lymphocytes and simultaneously had no effect on IFNγ expression, which is consistent with the viewpoint of Yun et al (2000). However, Laurent et al (2001) found that the IFNγ from CD8 + T lymphocytes was directly involved in the cellular immune response against coccidiosis in the test of broiler chicks infected with Eimeria tenella and Eimeria maxima. In addition, in piglets infected with circovirus type 2, dietary CLA inhibited the IFNγ expression in CD4 + T lymphocytes, but increased the IFNγ expression in CD8 + T lymphocytes (Bassaganya-Riera et al 2003).…”
Section: Discussionsupporting
confidence: 77%
“…In this experiment, dietary CLA did not change the percentage of duodenal CD4 + T lymphocytes and simultaneously had no effect on IFNγ expression, which is consistent with the viewpoint of Yun et al (2000). However, Laurent et al (2001) found that the IFNγ from CD8 + T lymphocytes was directly involved in the cellular immune response against coccidiosis in the test of broiler chicks infected with Eimeria tenella and Eimeria maxima. In addition, in piglets infected with circovirus type 2, dietary CLA inhibited the IFNγ expression in CD4 + T lymphocytes, but increased the IFNγ expression in CD8 + T lymphocytes (Bassaganya-Riera et al 2003).…”
Section: Discussionsupporting
confidence: 77%
“…Cell-mediated immunity plays a major role in resistance to parasite infections, and the cellular immunity against Eimeria infection could be transferred by spleen cells and PBLs to naive recipients in chickens (3)(4)(5)(6). Also, Eimeria infection induces high levels of IFN-g (7), which effectively inhibits the intracellular development of E. tenella (8), and upregulates mRNA expression of IL-1b, which recruits inflammatory cells including macrophages, neutrophils, and lymphocytes to the site of infection (7). Humoral immunity is equally important in parasite infections.…”
mentioning
confidence: 99%
“…Evidence from infection studies has suggested that chCXCLi1 and chCXCLi2 might have different roles (47,48). In both studies, chCXCLi1 was up-regulated to a higher level following Salmonella infection than chCXCLi2.…”
Section: New Chcxcr1 ------------------------------------------------mentioning
confidence: 62%